1972
DOI: 10.1128/jb.111.1.203-210.1972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Proline Analogues on the Formation of Alkaline Phosphatase in Escherichia coli

Abstract: Two of the four proline analogues tested for their effect on the formation and activity of Escherichia coli alkaline phosphatase were able to substitute for proline in protein synthesis in a proline auxotroph. One of these, 3, 4-dehydroproline, effectively replaced proline and led to formation of an active enzyme under conditions where no proline was present in the polypeptides. Substitution of azetidine-2-carboxylate for proline prevented active enzyme formation, producing instead altered monomeric forms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…These data help to explain our previous results describing increases in the amount of proteins in K-12 periplasmic fractions after starvation cultures for P1 (15). During exponential growth, about 5 to 7% of the cell protein can be found in the periplasmic fraction but this value increases to 15 to 20% upon starvation for P. Only one-third of the increase could be attributed to the alkaline phosphatase.…”
Section: Resultssupporting
confidence: 81%
“…These data help to explain our previous results describing increases in the amount of proteins in K-12 periplasmic fractions after starvation cultures for P1 (15). During exponential growth, about 5 to 7% of the cell protein can be found in the periplasmic fraction but this value increases to 15 to 20% upon starvation for P. Only one-third of the increase could be attributed to the alkaline phosphatase.…”
Section: Resultssupporting
confidence: 81%
“…Unlike most other proline analogues, the potent inhibitor 3,4-DHP functions at micromole concentrations to inactivate prolyl hydroxylase in vivo rapidly and irreversibly (Cooper and Vamer, 1983). Studies with an Escherichia coli proline auxotroph demonstrated that 3,4-DHP was the only Pro analogue tested that could replace proline in the synthesis of enzymically active acid phosphatase ( Morris and Schlesinger, 1972 ). For 3,4-DHP offers many advantages over other inhibitors, so it becomes a useful tool for studying the physiological and developmental functions of extensins among all types of HRGPs.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria also secrete proteins from the cell cytoplasm; in some strains these proteins appear in the culture medium whereas in others the polypeptides are retained in a region of the cell envelope referred to as the periplasmic space (23). In exponentially growing cultures of Escherichia coli K-12, 5 to 8% of the cell protein is in the periplasm (15,22). This value increases twoto threefold in E. coli mutants that have become constitutive for production of alkaline phosphatase, a normally repressed, periplasmic enzyme.…”
mentioning
confidence: 99%
“…This value increases twoto threefold in E. coli mutants that have become constitutive for production of alkaline phosphatase, a normally repressed, periplasmic enzyme. About half of the increase can be accounted for by the alkaline phosphatase alone (22).…”
mentioning
confidence: 99%